Sub-surface Biogeochemical Characteristics and Its Effect on Arsenic Cycling in the Holocene Gray Sand Aquifers of the Lower Bengal Basin - Ghosh, Devanita; Routh, Joyanto; Bhadury, Punyasloke (Frontiers in Environmental Science, 2017)
High arsenic (As) content in the fertile delta plains of West Bengal has been widely reported since the 1990s. The shallow grey sand aquifers (GSA) deposited during the Holocene, are more commonly used as potable water sources, but they have high As levels. The release of As into groundwater is influenced by indigenous microbial communities metabolizing different organic carbon sources present in the GSA sediments. After pre-screening the groundwater for assessing their microbial phylogenetic diversity, two50-m deep boreholes were drilled in the GSAs, and 19 sediment samples were recovered from each core. In each of these samples, grain-size distribution, sequential extraction, and quantification of trace metals and total extractable lipids were analyzed. The aquifer sediments consisted of medium to fine micaceous sand with clay lenses in between them; a thick clay layer occurred on top of both boreholes. Arsenic concentration in these sediments varied from 1.80 to 41.0 mg/kg and was mostly associated with the oxide and silicate-rich crystalline minerals. Arsenic showed a significant correlation with Fe in all fractions, suggesting the presence of Fe-(oxy)-hydroxides bound As minerals. The diagnostic lipid biomarkers showed presence of compounds derived from higher plants (epicuticular waxes) and microbial inputs. The biomarkers were abundant in clay and silt-rich layers. The samples indicated preferential preservation of n-alkanes over other functional compounds (e.g. alcohols and fatty acids), that are more reactive, and hence subject to further degradation. Sediments recovered from the borehole indicated the presence of Eustigmatophytes and vascular plant waxes that are mostly surface-derived. The sedimentary lipids also indicated the presence of complex petroleum-derived hydrocarbons. These compounds provide organic substrates, and support the preferential survival of specific microbial communities in these sediments.